Advances in Brain Inspired Cognitive Systems 6th International Conference, BICS 2013, Beijing, China, June 9-11, 2013. Proceedings - Liu, Derong; Alippi, Cesare; Zhao, Dongbin; Hussain, Amir.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Brain Inspired Cognitive Systems, BICS 2013, held in Beijing, China in June 2013. The 45 high-quality papers presented were carefully reviewed and selected from 68 submissions. BICS 2013 aims to provide a high-level international forum for scientists, engineers, and educators to present the state of the art of brain inspired cognitive systems research and applications in diverse fields.
Silhouette-based Gait Recognition via Deterministic Learning -- The global-local mental rotation in divided attention paradigm -- Research on Electromagnetic Coupling Artificial Neural Network with Spatial Topology -- EEG Signal Classification using the Event-related Coherence and Genetic Algorithm -- Effects of Emotional Content on Working Memory: Behavioral and Electrophysiological Evidence -- Ontology-based Collaborative Filtering Recommendation Algorithm -- Conceptual Clustering of Documents for Automatic Ontology Generation -- A Novel Clinical Expert System for Chest Pain Risk Assessment -- Fault Detection Filter Design for Certain Networked Control System -- Establishment of Tourism Geographic Information System to Promote Field Work in Tourism Management Major.
Keywords: Computer science; Database management; Information storage and retrieval systems; Artificial intelligence; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Database Management; Information Storage and Retrieval; Pattern Recognition; Computation by Abstract Devices